The ANC and Apartheid South Africa’s Nuclear Weapons Program - Jo-Ansie van Wyk; Anna-Mart van Wyk (The Thinker)
The African National Congress (ANC) was established in 1912 and banned by the apartheid government in 1960. Many members of the organisation went into exile, and it continued underground. The organisation became synonymous with the anti-apartheid and liberation struggle in South Africa until its unbanning in 1990. The organisation had early on adopted an anti-nuclear weapons position and its awareness of, and resistance against, the apartheid regime’s secret nuclear weapons program became one of the pillars of its global struggle to end apartheid. This paper traces the early development of the ANC’s position on nuclear energy and nuclear weapons, before discussing its international anti-nuclear initiatives, including its armed struggle and attack against the Koeberg nuclear power plant close to Cape Town, during its construction.